La valutazione: Il grande tabù educativo e sociale - Martínez-Maireles, David (Studi sulla Formazione/Open Journal of Education, 2024)
The reaction of disgust towards the term “assessment” depends on the individual mental representation constructed over time through life experiences. This article explores how assessment is socially and politically constructed by analysing perspectives for and against it. The aim is to propose a new outlook promoting a shift towards seeing assessment as a means of individual and collective improvement rather than merely punitive.